2005
DOI: 10.1002/art.21072
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning the care of fragility fracture patients to improve osteoporosis management: A health care improvement project

Abstract: Objective. To develop new processes that assure more reliable, population-based care of fragility fracture patients. Methods. A 4-year clinical improvement project was performed in a multispecialty, community practice health system using evidence-based guidelines and rapid cycle process improvement methods (plan-do-study-act cycles). Results. Prior to this project, appropriate osteoporosis care was provided to only 5% of our 1999 hip fracture patients. In 2001, primary physicians were provided prompts about ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 47 publications
3
64
0
4
Order By: Relevance
“…A majority of the focus group participants in the present study placed the responsibility for screening and management of GIOP on medicine subspecialists due to the limited time available to address multiple medical problems during a primary care clinic visit and the high likelihood that subspecialists will be treating patients needing long-term or high-dose steroids. A consensus among primary care and subspecialty providers needs to be reached so that responsibilities can be better defined to improve care provided to patients (16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A majority of the focus group participants in the present study placed the responsibility for screening and management of GIOP on medicine subspecialists due to the limited time available to address multiple medical problems during a primary care clinic visit and the high likelihood that subspecialists will be treating patients needing long-term or high-dose steroids. A consensus among primary care and subspecialty providers needs to be reached so that responsibilities can be better defined to improve care provided to patients (16).…”
Section: Discussionmentioning
confidence: 99%
“…Provider behavior, however, does not necessarily change based on treatment alerts alone. For example, in a study examining issues in osteoporosis management after the occurrence of bone fractures, Harrington and colleagues found that use of reminders and notification systems alone was not sufficient to alter provider behavior, and they recommended system and process changes to improve osteoporosis management (16). In this regard, it has been reported that providers are more likely to change medications for safety reasons if they are contacted by a pharmacist (54%) as opposed to receiving an electronic drug alert (4%) (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that vertebral fractures make up only a small proportion of FLS case loads [38][39][40][41][42][43][44][45], as shown in table 3. This is an important shortcoming which must be addressed because vertebral fractures are the most common fragility fracture and are underdiagnosed throughout the world [46].…”
Section: Secondary Fracture Preventionmentioning
confidence: 99%